2007
DOI: 10.1063/1.2821119
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric-constant measurement of thin insulating films at low frequency by nanoscale capacitance microscopy

Abstract: We demonstrate a method for quantitatively probing the local low-frequency dielectric constant of thin insulating films by nanoscale capacitance microscopy. The calibrated capacitance-distance curves are measured on the dielectric film and analyzed by using a tip-sample capacitance model here proposed. Applied to SiO2 films as small as 1×1μm2 area and 20–30nm thickness, the method gives a dielectric constant on the submicron scale in agreement with the value determined on the large scale. The observed precisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
176
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(193 citation statements)
references
References 15 publications
14
176
0
3
Order By: Relevance
“…Among them, we can cite nanoscale capacitance microscopy [1][2][3], electrostatic force microscopy (EFM) [4][5][6][7][8][9][10], nanoscale impedance microscopy [11,12], scanning polarization force microscopy [13][14][15][16], scanning microwave microscopy (SMM) [17,18] and nanoscale non-linear dielectric microscopy [19]. These techniques have allowed measuring the electric permittivity with nanoscale spatial resolution on planar samples, such as thin oxides, polymer films and supported biomembranes [2][3][4]8,10], and on non-planar ones, such as, single carbon nanotubes, nanowires, nanoparticles, viruses and bacterial cells [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, we can cite nanoscale capacitance microscopy [1][2][3], electrostatic force microscopy (EFM) [4][5][6][7][8][9][10], nanoscale impedance microscopy [11,12], scanning polarization force microscopy [13][14][15][16], scanning microwave microscopy (SMM) [17,18] and nanoscale non-linear dielectric microscopy [19]. These techniques have allowed measuring the electric permittivity with nanoscale spatial resolution on planar samples, such as thin oxides, polymer films and supported biomembranes [2][3][4]8,10], and on non-planar ones, such as, single carbon nanotubes, nanowires, nanoparticles, viruses and bacterial cells [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…6 we have demonstrated that by performing calibrated C͑Z͒ curves on a homogeneous and uniformly thick dielectric film ͑see Fig. 6 below͒, the ratio h / r can be extracted in a very quantitative way at the nanoscale.…”
Section: A Capacitance Versus Distance Measurementsmentioning
confidence: 99%
“…The remaining contributions conform the stray capacitance contribution that can be subtracted from the experiments following an appropriate calibration procedure as previously reported. 1,6,10 In order to arrive at an analytical expression for the apex capacitance in the presence of a thin dielectric film, we will restrict ourselves to the model system depicted in Fig. 1͑b͒.…”
Section: A Theoretical Derivationmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be reduced further by a better screening, but this is not trivial due to the high temperature. Thus, it is not likely that the values in the aF range achieved [7,8] at room temperature can be obtained. The upper limit is set by the 1 M overload protection resistor.…”
Section: Conductance Mappingmentioning
confidence: 99%